Outcome of catheter ablation in the very elderly‐insights from a large matched analysis. Issue 12 (31st August 2020) - Willy, Kevin; Frommeyer, Gerrit; Dechering, Dirk G.; Wasmer, Kristina; Höwel, Dennis; Welle, Sarah S.; Bögeholz, Nils; Ellermann, Christian; Wolfes, Julian; Rath, Benjamin; Leitz, Patrick R.; Köbe, Julia; et al.
Abstract: Background: Ablation emerged as first line therapy in the treatment of various arrhythmias. Nevertheless, in older patients (pts), decision is often made pro drug treatment as more complications and less benefit are suspected. Hypothesis: We hypothesized that different kind of ablations can be performed safely regardless of the pts age. Methods: We enrolled all pts aged >80 years (yrs) who underwent ablation for three different arrhythmias (atrial flutter [AFL], atrioventricular nodal re‐entry tachycardia [AVNRT], ventricular tachycardia [VT]) between August 2002 and December 2018. Procedural data and outcome were compared with matched groups aged 60 to 80 years and 40 to 60 years, respectively. Periprocedural and in‐hospital complications were analyzed. Results: The analysis included 1191 patients (397 pts per group: 63% AFL, 23% AVNRT, 14% VT) who underwent ablation. Acute success was high in all types of arrhythmias irrespective of age (>80, 60‐80, 40‐60 years: AFL 97%/98%/98%, AVNRT 97%/95%/97%, VT 82%/86%/93%). Rate of periprocedural complications were similar in all groups treated for AFL and AVNRT. For VT ablations significant differences were noted between pts > 80 or 60 to 80 years and those aged 40‐60 years (16.1%/14.3%/3.6%). Most complications were infections and groin haematoma. No strokes, iatrogenic atrioventricular blocks and deaths related to the ablation occurred. Conclusion: Ablation appears safe in pts > 80 years. Success rates were comparable to matched younger cohorts. A significant difference was observed for VT patients.